Factors Related to the Utilization of Health Services in the Working Area of Wee Luri Public Health Center, Central Sumba District - Ola, Desry; Sinaga, Masrida; Kenjam, Yoseph (Faculty of Public Health, Nusa Cendana University, 2024)
Health is an important element in human life. Utilization of health services is any effort carried out individually or together, in an organization to maintain and improve health, prevent and cure illnesses and restore the health of individuals, families, groups and communities. The utilization of health services in the community in the working area of the Wee Luri Health Center, Central Sumba Regency, is still relatively lacking due to the community's perception of illness. People come to the Wee Luri Health Center when the illness is severe enough. The community assumes that the public health center is for those whose illness is severe in the sense that they are unable to get up from bed This study aimed to determine the factors influencing the utilization of health services in the Wee Luri Health Center working area, Central Sumba Regency, in 2020. Using a descriptive survey and cross-sectional design, the study involved 153 families, with family heads selected through simple random sampling. Data analysis using the Chi-Square test (α = 0.05) revealed significant relationships between education (p = 0.028), insurance ownership (p = 0.001), accessibility (p = 0.010), knowledge (p = 0.005), and perception of illness (p = 0.040) with health service utilization.Wee Luri Health Center needs to further improve health promotion and the quality of health services in order to increase public knowledge and provide comprehensive and integrated services.